2017
DOI: 10.1111/1462-2920.13683
|View full text |Cite
|
Sign up to set email alerts
|

Ecotype diversification of an abundant Roseobacter lineage

Abstract: The Roseobacter DC5-80-3 cluster (also known as the RCA clade) is among the most abundant bacterial lineages in temperate and polar oceans. Previous studies revealed two phylotypes within this cluster that are distinctly distributed in the Antarctic and other ocean provinces. Here, we report a nearly complete genome co-assembly of three closely related single cells co-occurring in the Antarctic, and compare it to the available genomes of the other phylotype from ocean regions where iron is more accessible but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 120 publications
(190 reference statements)
0
20
0
Order By: Relevance
“…While most roseobacters have large genomes with diverse metabolic and regulatory capabilities, HTCC2255 has a relatively small genome (half the size and number of genes typical of roseobacters), and a relatively restricted set of metabolic capabilities and transcriptional regulators (Newton et al, 2010;Luo and Moran, 2014) suggestive of a more specialist, oligotrophic lifestyle (Giovannoni et al, 2014;Billerbeck et al, 2016). While most Roseobacter genomes lack photo-driven supplemental energy conservation or use aerobic anoxygenic phototrophy, HTCC2255 is one of the only Roseobacter genomes to contain a proteorhodopsin (Newton et al, 2010;Sun et al, 2017).…”
Section: Roseobactersmentioning
confidence: 99%
“…While most roseobacters have large genomes with diverse metabolic and regulatory capabilities, HTCC2255 has a relatively small genome (half the size and number of genes typical of roseobacters), and a relatively restricted set of metabolic capabilities and transcriptional regulators (Newton et al, 2010;Luo and Moran, 2014) suggestive of a more specialist, oligotrophic lifestyle (Giovannoni et al, 2014;Billerbeck et al, 2016). While most Roseobacter genomes lack photo-driven supplemental energy conservation or use aerobic anoxygenic phototrophy, HTCC2255 is one of the only Roseobacter genomes to contain a proteorhodopsin (Newton et al, 2010;Sun et al, 2017).…”
Section: Roseobactersmentioning
confidence: 99%
“…Considering that Fe-limitation typically results in a decline in energy levels within the cell (Tortell et al 1999), a possible link may exist between PR-based phototrophy and the ability to enhance energy production within Fe-limited cells (Raven 2009;Marchetti et al 2012Marchetti et al , 2015Sun et al 2017;Cohen et al 2018). The formation of a proton gradient by the PR photosystem does not require Fe, while phototrophic systems containing Type I and Type II reaction centers, such as those found in oxygenic phototrophs, require Fe-containing cytochromes in order to sustain electron flow (Blankenship 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a proton gradient by the PR photosystem does not require Fe, while phototrophic systems containing Type I and Type II reaction centers, such as those found in oxygenic phototrophs, require Fe-containing cytochromes in order to sustain electron flow (Blankenship 2010). The comparison of three closely related Roseobacter strains, indicated that the two strains isolated from Fe-replete regions contained a Type II reaction centre (bacteriochlorophyll complex), while the strain isolated from an environment characterised by Fe-limitation (Antarctic waters) contained a PR gene (Sun et al 2017). It was hereby suggested that the presence of a PR gene was a potential adaptation for a Roseobacter strain subjected to low Fe-concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Genomes from strains WA and WB, together with those from 33 other bacterial strains from the Clostridium genus and an outgroup strain ( Bacillus licheniformis ATCC 14580) affiliated to the same Clostridiaceae family were analyzed to establish their phylogenetic relationship. By referring to the method from Sun et al [ 65 ], a Clostridial phylogenetic tree was finally constructed with the LG substitution matrix and the gamma model using the RAxML tool (V8.0) based on a concatenation of 10793 amino acid sites over 129 single-copy gene families shared by 36 available genomes [ 38 ] and finally demonstrated via MEGA6 [ 66 ].…”
Section: Methodsmentioning
confidence: 99%